2017
DOI: 10.1039/c7ra00734e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcination temperature on the structure and catalytic performance of copper–ceria mixed oxide catalysts in phenol hydroxylation

Abstract: We report on highly active CuO@CeO2 catalysts prepared by the surfactant-template method and calcined at different temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 60 publications
5
27
0
4
Order By: Relevance
“…Two different O species with peaks centered around 528 eV and 530 eV were observed. The first one is characteristic of the lattice oxygen forming the fluorite structure with cerium, whereas the second one can be attributed to the oxygen bound to carbon components 44 . This result is in agreement with C 1s XPS spectrum, which is exhibited in Figure 4C.…”
Section: Resultssupporting
confidence: 87%
“…Two different O species with peaks centered around 528 eV and 530 eV were observed. The first one is characteristic of the lattice oxygen forming the fluorite structure with cerium, whereas the second one can be attributed to the oxygen bound to carbon components 44 . This result is in agreement with C 1s XPS spectrum, which is exhibited in Figure 4C.…”
Section: Resultssupporting
confidence: 87%
“…Employing the used catalyst, the above test reaction was performed again under the same conditions. As shown in Figure , the reused catalyst showed only slight deactivation after five cycles, which might have been caused by gradual poisoning of the catalyst and block of its pores by tar formed during reaction . This result showed that the CuMgFe–LDHs had good reusability and potential industrial value in phenol hydroxylation.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the calcination temperature is one of the key parameters influencing the structural as well as the surface area of the material. By increasing of calcination temperature until optimum condition will dramatically enhance the surface area of material as studied by Amadine et al 17 . Therefore, the adsorption ability of material will be enhanced as a result of surface area improvement.…”
Section: Bekonang Clay and Andisol Soil Composites Pranoto Pranoto Etmentioning
confidence: 99%